Упровадження системи бюджетування на шляху досягнення беззбитковості та високої конкурентоспроможності промислових підприємств України - Даниленко, О.В. (Економічний вісник Донбасу, 2014)
Автор розглядає бюджетування як шлях до підвищення рентабельності промислових підприємств та їх конкурентоспроможності в умовах актуальної кон’юнктури ринку. Автор рассматривает бюджетирование как способ повышения рентабельности промышленных предприятий и их конкурентоспособности в условиях актуальной конъюнктуры рынка. The author considered budgeting as the means of rise of profitability of the industrial enterprises and their competitive strategy under the actual economical conditions in the market. The carried out analysis lets us come to the conclusion that the problem of the rise of profitability and competitive strategy of the metallurgical complex of Ukraine as the leading sector of economy becomes even more actual under the conditions of the further aggravation of the world economic crisis and the entry to the world market of such strong players as China and India. Cost control and expenses limitation with the help of qualitative budgeting system being in accordance with contemporary world tendencies and complex approach to the definition of basical financial indicators of the activity planning and also the definition of clear-cut scheme of the financially responsible centers and the number of the budget process participants – all this will give the possibility to decrease the cost price of output that will lead to the additional advantages in the competitive struggle of the domestic metallurgical enterprises and will increase its investment attractiveness in the world market.